Jack Reacher : Never Go Back - Book 18 - Child, Lee; Hill, Dick; Gildea, Kelly; Random House Audio Publishing (New York : Random House Audio, 2013)
Former military cop Jack Reacher makes it all the way from snowbound South Dakota to his destination in northeastern Virginia, near Washington, D.C.: the headquarters of his old unit, the 110th MP. The old stone building is the closest thing to a home he ever had. Reacher is there to meet--in person--the new commanding officer, Major Susan Turner, so far just a warm, intriguing voice on the phone. But it isn't Turner behind the CO's desk. And Reacher is hit with two pieces of shocking news, one with serious criminal consequences, and one too personal to even think about.
Keywords: Reacher, Jack (Fictitious character) -- Fiction; Retired military personnel -- Fiction; Military police -- Fiction; Murder -- Fiction -- Investigation; Audiobooks; Suspense fiction; Audiobooks